2014
DOI: 10.1016/j.whi.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Linking Nontraditional Physical Activity and Preterm Delivery in Urban African-American Women

Abstract: Background Traditional risk factors for preterm delivery (PTD) do not account for the disparate rates among African-American women. Physical activity during pregnancy may protect women from PTD, but few studies exist in African Americans. Our objective was to examine the relationships between PTD and intensity and duration of leisure time physical activity (LTPA) as well as non-LTPA such as stair climbing and walking for a purpose during pregnancy. Methods Data were from a hybrid retrospective/prospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…Five cohort studies 34,39,44,49,51 and two randomized trials 64,65 were included in the analysis of walking during pregnancy and preterm birth, and included 1065 cases and 26 903 participants. The summary RR for high versus low walking was 1.09 (95% CI: 0.68-1.75, I 2 = 72.3%, P heterogeneity < 0.0001; Figure 4E).…”
Section: Walking During Pregnancymentioning
confidence: 99%
“…Five cohort studies 34,39,44,49,51 and two randomized trials 64,65 were included in the analysis of walking during pregnancy and preterm birth, and included 1065 cases and 26 903 participants. The summary RR for high versus low walking was 1.09 (95% CI: 0.68-1.75, I 2 = 72.3%, P heterogeneity < 0.0001; Figure 4E).…”
Section: Walking During Pregnancymentioning
confidence: 99%
“…For studies that had sufficient statistical power to explore strenuous leisure activity (typically as any vs none), there was no effect or a modestly reduced risk of preterm birth 48 50–52…”
Section: The Effect Of Exercise On the Fetusmentioning
confidence: 99%
“…A recent meta-analysis found that women with depression were more likely to have preterm birth (RR= 1.24, 95%CI: 1.04-1.47)(Grote et al, 2010). In contrast, a recent study reported that African-American women who walked for a purpose for more than 30 minutes per day during pregnancy had lower risk of preterm birth (Sealy-Jefferson et al, 2014). To our knowledge, this is the first study to examine the mediating effect of walking for a purpose on the effects of symptoms of depression on gestational age at birth.…”
Section: Discussionmentioning
confidence: 96%
“…In a prior study of low income African-American women in Baltimore, the researchers found an increased odds of preterm birth for women who walked for a purpose four days or more per week (Misra, Strobino, Stashinko, Nagey, & Nanda, 1998). In contrast, another study in the same city (different institution) reported that African-American women who walked for a purpose for more than 30 minutes per day during pregnancy had lower risk of preterm birth (Sealy-Jefferson, Hegner, & Misra, 2014). Misra and associates (1998) defined walking for a purpose as the average number of days per week in the first and second trimesters combined that a woman spent walking for a purpose and did not collect duration of walking for a purpose (i.e., minutes per day).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation